Respons Tanaman Sorgum atas Aplikasi Mikoriza Arbuskula pada Gradien Konsentrasi N dan P - Devanda Ayu Lidya Permata Putri; Rahayu Widyastuti; Idris Idris; Azra Zahrah Nadhirah Ikhwani; Satya Nugroho; I Made Sudiana; Atit Kanti; Masaru Kobayashi (Institut Pertanian Bogor, 2023)
Sorghum [Sorghum bicolor (L.) Moench] is a multipurpose food crop that can adapt to climate change. Sorghum productivity can be increased by applying chemical fertilizers and arbuscular mycorrhiza fungi (AMF). This research aimed to assess the effect of AMF application and N and P concentration gradients to support Super 2 and KS sorghum accession growth. The plants were grown in a sterilized zeolite (coarse and fine) and inoculated with Glomus mosseae 40 spores per pot. The experimental design was a randomized complete block design with 40 treatments and three replications. N and P concentration gradient treatments were carried out using a dose level of fertilizer N (urea) and P (TSP) at 12,5%; 50%; 75%; 100%; and 125%. Analysis of variance was carried out using SAS 9.0 software at a level of 5%, and the results were significantly different, followed by DMRT. The application of AMF and urea 50% and TSP 75% in Super 2 accessions and urea 50% and TSP 50% in KS accessions gave the highest plant height and biomass. However, the increase in sorghum growth did not correlate with root colonization and root length, which could be seen that the highest in both accessions were obtained at urea 12,5% and TSP 12,5%. The application of AMF can significantly lower the use of urea and TSP fertilizers by up to 50% compared to a positive control (urea and TSP 100%) and support sorghum growth in both accessions. Keywords: Glomus mosseae, Konawe Selatan accession, Super 2 accession, TSP, urea